Investigation on Strength Development in RBI Grade 81 Stabilized Serian Soil with Microstructural Considerations - Taib, S.N.L.; Striprabu, S.; Ahmad, F.; Charmaine, H.J.; Patricia, N.E. (IOP Publishing Ltd, 2016)
The aim of the research is to investigate the strength development of stabilised local Serian soil with RBI Grade 81 a chemical additive to enhance soil properties in term of strength. Serian is a town which is located about 60 km from Kuching city where the soil was chosen to be treated in this study. The soil sample was mixed with 2 %, 6 % and 8 % of RBI Grade 81 by weight of dry soil and added with water at optimum water content (OWC) to replicate field site conditions. The modified samples were cured in ambient air for 7, 14, and 28 days. Scanning Electron Microscope (SEM) was utilized to analyze surface morphology of the stabilized soil specifically on the formation of bonding between soils and RBI 81 particles. The experimental results show the highest average peak UCS strength achieved was 1071.6 kN/m2 at 14 day curing period with 8 % of RBI Grade 81 which is higher than the untreated control sample which was 179.946 kN/m2, showing increment by almost six folds. Hence the RBI 81 stabilization technique enhances the local soil structure by improving the inter-cluster bonding, reducing pore spaces in the soil and subsequently increasing the soil’s strength.